KONSEP KHILAFAH DALAM EKONOMI ISLAM DAN IMPLIKASINYA TERHADAP KEPEMILIKAN - Rusdan (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2025)
The term "khilafah" is commonly used in the context of Islamic politics and governance, representing a singular governing system in Islam (Islamic khilafah). Its objective is to uphold Islamic law (sharia) and propagate Islamic teachings globally. Recently, the term has extended to Islamic economics with adapted meanings. This study focuses on the concept of khilafah in Islamic economics and its implications for ownership. Conducted as qualitative research, it involves written data, such as relevant documents, and employs library research or book surveys for data collection. In the realm of Islamic economics, the khilafah concept is closely tied to humanity's role as representatives of Allah SWT, particularly in managing wealth and the universe. The first implication of the khilafah concept on ownership is the relative and delegated nature of human ownership over wealth, with Allah SWT as the ultimate owner. Consequently, every economic decision made by humans, acting as representatives of Allah SWT, to prosper the universe must align with Allah SWT's guidelines. The second implication involves the social rights of others over an individual's wealth, encompassing obligatory rights like zakat and voluntary contributions such as infaq, shadaqah, and other charitable acts.